Challenges and Opportunities for Digital Transformation in Philippine Microfinance Institutions - Binaluyo, Jonathan P.; Santos, Angelo R.; Agustin, Noel B. (International Journal of Economics and Financial Issues, 2024)
The research focuses on the factors that affect the digital transformation of Microfinance Institutions in Nueva Ecija, Philippines. The research objective is to evaluate the performance and digital progress made by the MFIs currently to measure the effectiveness of the guidelines and to identify recommendations for further improvement. In this study, descriptive research design was employed, and data were generated from 205 MFI Clients and owners by administering questionnaires and interviews. The research shows that its use in business leads to increased operational efficiency, quality delivery, and positive client experience. However, there are issues that need to be faced, including issues like data security or the high costs of the necessary infrastructure and lack of adequate infrastructure in certain regions. Based on the findings of the study, the following recommendations can be made: The establishment of powerful financial literacy programs that banks can support and facilitate, modification of the current credit bureau functionalities, more comprehensible and easier to use digital platforms that consumers can use in their interaction with the banks, and better cybersecurity. Further, the state should support such policies and regulation to help the countries in embarking on digital transformation. The study proves the need to carry out further studies on the development of digital financial services to enhance financial inclusion and socio-economic growth. Its suggested that, by adopting these measures, MFIs will be in a position to help their clients achieve the desired economic outcomes, especially in the rural settings.